2013
DOI: 10.3109/01443615.2013.813913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depression and anxiety on the success of pelvic floor muscle training for pelvic floor dysfunction

Abstract: The objective of this study was to determine the impact of the psychiatric symptoms of anxiety and depression, as assessed by validated questionnaires on the success of pelvic floor muscle training (PFMT). A prospective observational study was carried out by the Uro-gynaecological Physiotherapy Department at the Singleton Hospital, Swansea. A total of 108 consecutive women with pelvic floor dysfunction were referred for physiotherapy and admitted to the 6-month physiotherapy programme. They underwent subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 15 publications
2
34
0
1
Order By: Relevance
“…The emotional centers in the brain can affect motility and sensation in the gut, acting mainly via the hypothalamic-hypophyseal axis and brain-gut axis. Studies have shown that depression increases pelvic floor muscle tension and reduces rectal sensitivity [45,46]. Mild depression can be relieved to some extent by psychological counseling and by explanation of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The emotional centers in the brain can affect motility and sensation in the gut, acting mainly via the hypothalamic-hypophyseal axis and brain-gut axis. Studies have shown that depression increases pelvic floor muscle tension and reduces rectal sensitivity [45,46]. Mild depression can be relieved to some extent by psychological counseling and by explanation of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic organ prolapse (POP) is a common medical problem in women and is classified as anterior, posterior vaginal wall prolapse, uterus (cervix) or apical vaginal prolapse, and/or enterocele; these forms are often coexistent. Women with POP usually experience one or more discomforts involving a feeling of pelvic heaviness, fullness or low back pain, or voiding and/or defecation dysfunction; these symptoms greatly affect quality of life and can even result in social, psychological, and sexual problems . Estimates of prevalence of POP in the general population range from 2.9% to 50% due to the lack of a standard definition, differences in the demographic characteristics of the surveyed population, and imperfect records .…”
Section: Introductionmentioning
confidence: 99%
“…Women with POP usually experience one or more discomforts involving a feeling of pelvic heaviness, fullness or low back pain, or voiding and/or defecation dysfunction; these symptoms greatly affect quality of life and can even result in social, psychological, and sexual problems. 1 Estimates of prevalence of POP in the general population range from 2.9% to 50% due to the lack of a standard definition, differences in the demographic characteristics of the surveyed population, and imperfect records. [2][3][4] Approximately, 300,000 surgeries for prolapse are performed annually in the United States 5 ; however, over the next 30 years, the demand for services to care for female pelvic floor disorders is expected to increase at twice that of the same population.…”
Section: Introductionmentioning
confidence: 99%
“…Although physical and psychological factors both produce drug non-persistence, physical dysfunction is not its primary predictor (Dumoulin et al, 2010;Hay-Smith & Dumoulin, 2006), contrasting with psychological variables (e.g., depression, anxiety) that play key roles (Goode et al, 2008;Khan et al, 2013;Osborne et al, 2016). Although development of β3-adrenoceptor agonists, that have fewer side effects, helps overcome the problems associated with older antimuscarinic drugs (Thiagamoorthy et al, 2016), such an Hypnotherapy for OAB -4 approach does not address the psychological factors that can determine therapy nonadherence (DiMatteo et al, 2000).…”
mentioning
confidence: 99%